Sustainable Innovate Strategy and Customer Satisfaction in Small- and Medium-Sized Enterprises (SMEs) in Nigeria. - Timilehin Olasoji Olubiyi (International Journal of Small and Medium Enterprises and Business Sustainability, 2022)
The coronavirus pandemic has resulted in extraordinary shocks to businesses with unfavorable effects on their current capacities. To maintain a business competitive advantage, providing sustainable innovative products or services is inevitable. Small and medium-sized enterprises' survival, customer satisfaction, and lack of longevity continue to spark public debate and scholarly interest. Inadequate innovative strategy is one of the key problems to which poor customer satisfaction may be attributed. The purpose of conducting this particular study is to find out the relationship between innovative strategy and sustainable customer satisfaction amongst selected small and medium-sized enterprises in Lagos State. This paper conducted a survey research approach, using a sample size of 742, consisting of owner-managers of selected SMEs in Lagos State. Data was gathered using a standardized questionnaire that was adopted and validated for the research. The Cronbach's alpha coefficient for the questionnaire items varies from 0.77 to 0.88. The response rate to the questionnaire was 92.6%. The collected data was analyzed using descriptive and inferential statistics (Pearson product-moment correlation and regression analysis). The analysis of the data showed that in Lagos State, there was a strong link between innovative strategy and customer satisfaction (= 0.090, t = 3.029, F = 9.176, p <0.05). This paper concluded that innovative strategy is a resource that improves customer satisfaction, sustainability, and business performance with theoretical and practical implications. It is recommended that SMEs in Lagos State incorporate innovative strategy and sustainability into their strategic vision and plans to enhance competitive advantage, since it may be beneficial for the environment, marketing, product and service developments.